Effect of Washing on Reducing Bacterial Loads in Common Vegetables Sold in Dhaka City (Bangladesh Journal of Microbiology, 2019)
Vegetables and fruits can be contaminated with microorganisms from different sources during production and processing. Quality of vegetables usually relies on the quality of processing water and sanitizers used to reduce microbial load and increase shelf-life of vegetables. The present study demonstrates the role of washing on reducing bacterial loads in common vegetables sold in Dhaka city. A total of seventy two samples comprising of eighteen types of fresh vegetables were collected. Total heterotrophic bacteria, coliforms and Enterobacteriaceae were determined in 72 samples including potato, tomato, carrot, cucumber, green chilli, bean, eggplant, cauliflower, turnip, radish, capsicum, pumpkin, cabbage, gourd, papaya, bitter gourd, snake gourd and ridge gourd before and after washing with tap and filtered water, halotab water, bleaching powder (0.2%) solution and bleaching powder (0.2%) with citric acid (0.1%) for 10 minutes. Tap water, filtered water, bleaching powder (0.2%), halotab solution and bleaching powder (0.2%) + citric acid (0.1%) solutions were found to be effective and significantly reduced the bacterial loads in vegetables compared to the unwashed vegetables (P